The role of cruelty-free and vegan logos on purchase intention : investigating the effects of certification, logo recognizability and pro-environmental attitude - Cardoso, Bárbara Marques Freire (2022)
As consumers become increasingly aware of the negative environmental consequences of buying certain products, they demand more transparency and responsible behaviors from manufacturers. In this context, eco-labels emerge to empower shoppers with knowledge so that they can make informed sustainable purchases. However, since there is a vast number of eco-labels on the market, brands need to choose wisely the logos that will add some value to customers, in terms of environmental implications, without overwhelming or growing mistrust. This dissertation aims to clarify how eco-label communication impacts the purchase intention of skincare by using two types of logos: cruelty-free and vegan. It further explores if certification influences consumers’ buying decisions. For such, an online survey was distributed, and the results indicated that logo communication has a positive impact on purchase intention, as does certification. However, the two logos used did not show significant differences between them. Hence we argue that different claims do not matter in this case. Additionally, other variables were incorporated. Logo recognizability exhibited a positive effect on purchase intention, and pro-environmental attitude moderated the relationship that eco-labels have on the willingness to purchase. In conclusion, this study gives marketers relevant insights on how they can increase purchase intention by incorporating eco-labels in their products, which can be translated into higher sales volume.